Panel Great Saphenous Vein Reconstruction in Emergency: A Case Report and Literature Review of Traumatic Venous Injuries - Adharsh Kumar Maruthu Pandian; S K Balaji; D N Sharmila; C Saravanan Robinson; Roy Christo; Poorna Raj; Manojh; Krishna Prasad Yadav (Indian Journal of Vascular and Endovascular Surgery)
Vascular injury of the lower limbs is considered one of the common vascular traumas in our locality. Management of vascular extremity trauma remains challenging and has no fixed algorithms of management. A young male presented to us with bull gore traumatic injury to the femoral vein. We repaired the injury with panel great saphenous vein (GSV) graft in the emergency setting. Ligation or repair (venorrhaphy/interposition) of venous injury in traumas has always been a controversy. Herein, we discuss briefly the available literature on venous injuries and why we preferred panel over spiral GSV graft repair.